2001
DOI: 10.1111/1467-8535.00222
|View full text |Cite
|
Sign up to set email alerts
|

Building a theoretical framework of web‐based instruction in the context of distance education

Abstract: This study attempts to analyze teaching and learning processes of web-based instruction (WBI) as shown in recent literature, and to develop a theoretical framework of WBI using a prominent existing distance education theory called Transactional Distance Theory in order to provide better understanding of the essential pedagogical components of WBI. Recent studies have shown that the key elements of the structure of WBI are (1) content expandability, (2) content adaptability, and (3) visual layout. And also thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 24 publications
1
67
0
7
Order By: Relevance
“…It may be that students making these comments perceive a lack of stimulus due to the loss of nonverbal communication and the lack of physical contact with their peers and instructor. Student responses in this project affirmed the work of Chen and Willits (1999) and Jung (2001), who show the value of supporting effective forms of interaction between learner-instructor, learner-learner, and learner-content. Student experiences in our virtual classrooms demonstrated that varied processes of real-time communication, which are sensitive to individual learning preferences, positively affected some student involvement in online learning.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It may be that students making these comments perceive a lack of stimulus due to the loss of nonverbal communication and the lack of physical contact with their peers and instructor. Student responses in this project affirmed the work of Chen and Willits (1999) and Jung (2001), who show the value of supporting effective forms of interaction between learner-instructor, learner-learner, and learner-content. Student experiences in our virtual classrooms demonstrated that varied processes of real-time communication, which are sensitive to individual learning preferences, positively affected some student involvement in online learning.…”
Section: Discussionsupporting
confidence: 54%
“…In online contexts, instructors must strive to optimize interaction between learner-instructor, learner-learner, and learner-content through effective modes of communication (Chen & Willits, 1999;Jung, 2001;Moore, 1993). The facilitation of dialogue involves an evaluation of the opportunities for dialogue as well as an analysis of the quality of the dialogue that occurs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Most of these studies have had "common shortcomings" in that they have failed to develop a theoretical or conceptual framework of web-based, or online instruction (Jung, 2001). Indeed, the process of designing online instruction can be so complex and difficult that educators often end up adopting curriculum to fit the technology rather than selecting the proper technology to support the curriculum.…”
Section: Challenges In E-learningmentioning
confidence: 99%
“…In analyzing the pedagogical components of webbased instruction, Jung (2001) utilizes the transactional distance theory. According to this theory, there are three key constituent elements that define every distance education program: dialogue, structure, and learner autonomy.…”
Section: Distance Learning: a Surveymentioning
confidence: 99%